THE ONOMASIOLOGICAL MATRIX IN THE DERIVATIVE FUNCTION OF THE SUFFIXES OF THE DENOMINATIVE VERBS IN THE OLD UKRAINIAN LANGUAGE OF THE 14th–17th CENTURIES - Kocherga, Halyna (Linguistic Bulletin (Movoznavchyi Visnyk), 2023)
The article analyzes the mechanism of secondary designation of the suffix-verb derivation of the Old Ukrainian written monuments of the 14th–17th centuries, establishes the limits of semantically derived units in the nominative-derivative processes of the national-linguistic picture of the world, which constitute a significant part of the lexical composition of the language base, since numerous word-forming models of modern languages were formed in the past and went through a difficult path in their functioning, intensifying or losing their productivity, reflecting all spheres of life of the ancient Ukrainian society. The suffixed wordform of the denominative verbs should be considered not only within the limits of semantics, but also in the onomasiological aspect of language and its connections with the structure of consciousness: thinking, mental functions, internalization of reality and the feeling of the world, as well as in the mechanism of reflecting referents in the mentality and marking them in language system. That is why the place of this or that wordformation model in the complex and branched word-formation system of the modern Ukrainian language can be determined based on the history of the language, because the language suffix segment reflects the thinking of a person of the Middle Ages, his perception and evaluation of the phenomena of extra-linguistic reality and the linguistic picture of the world in particular. The scientific originality of the work lies in the fact that it is the first to analyze the system of word-forming types of the denominative verbs on the basis of significant material selected from written sources of the Old Ukrainian period of the 14th–17th centuries of the history of the Ukrainian literary language. The purpose of the study is to find out the internal structure of the suffixal subsystem of the denominative verbs of the Old Ukrainian language of the 14th–17th centuries and to establish a motivational matrix in derivatives that forms a word-forming model of nomination. We continue a series of publications on the formation of the verb system of the Old Ukrainian (Rus) language of the 14th–17th centuries, taking into account the semantic-categorical modifications of suffixed verbs with the status of a word, implemented in the onomasiological mechanisms of the verbal word-form of written monuments of the 14th–17th centuries at the level of conceptual relations of the synergistic system of ethnic consciousness of the speaker. Research materials, methods and techniques. For the research were used the “Materials for the Dictionary of the Written and Book Ukrainian Language of the 15th–18th Centuries”: in 2 books. /E. Tymchenko [Cf. V. V. Nimchuk, G. I. Lysa]. NAS of Ukraine, Ukrainian Free Academy of Sciences in the USA. Kyiv; New York, 2002–2003. [Memorials of the Ukrainian language. Series of dictionaries]. Book 1–2. The research methodology is outlined by the complex use of methods used in modern linguistics, in particular descriptive, component, transformational, distributive, comparative, valence, comparativehistorical methods of researching the semantic structure of the verb units. The suffixed word-form of nominative units in the diachronic aspect (based on the material of written records) is declared by the description models of the combined approach to comparative research (onomasiological with elements of field and ideographic), which demonstrates a two-vector analysis, from a thought to a word and from a word to a thought, detailed cognitively a discursive approach in the emergence of new derived units with the status of a word in the linguistic conceptualization of the world with a projection into the pragmatic plane. The above-mentioned areas of the historical derivational research state noticeable changes in the conceptual and terminological derivational apparatus, produce a new interpretation of the basic word-forming categories on the basis of general theoretical considerations using traditional sources (mainly written records), which constitute the relevance and perspective of this research. The onomasiological nature of the derivational suffix processes of the emergence of derived verb units in the linguistic subsystem of the Old Ukrainian literary language of the 14th–17th centuries has been clarified. Nominative processes determine the mechanism of interaction between reality, thinking and language. Conclusions and prospects of the study. The verb system of the Old Ukrainian language of the 14th–17th centuries makes it possible to establish that verbal nominatives formed from nouns with the help of verbal suffixes -и-…, -а-(ѧ), -ѣ- (˃ -і-), - ова-, (˃-ува-/ -юва-, - ева -///- ева-/) produce different ways of creating words, different word-forming resources, demonstrate a wide structural and motivational array of derived verb units that actively functioned in the Old Ukrainian period and, undoubtedly, qualify and shape the word-forming suffix subsystem of verbs in the modern Ukrainian literary language. A large group of pronominal verb derivatives in the Old Ukrainian literary language of the 14th–17th centuries were verbal formations from noun bases (of pronominal and adjectival origin). These derivative formations are divided into two categories: 1) verbs that were de-etymologized and ceased to be recognized as derivatives due to the decline of the main word or the destruction of the semantic connection with it; 2) verb units in which the motivational connection with the main word is clearly visible. Verbal suffix nominates of the written monuments of the Old Ukrainian language of the 14th–17th centuries are material for understanding the processes of conceptualization, verbalization, categorization, the functionality of the dynamics of wordformative changes in the verb system of the Ukrainian language, changes in the sem structure of verbs, reorientation to other word-formants, the semantic core of which, related to the mental processes of ethnoand glottogenesis of the Ukrainian ethnos. We see the prospect of further studies primarily in a comprehensive study of the derivational system of the Ukrainian verb in terms of the diachrony of prefix creation in the cognitive-onomasiological aspect.